THE URGENCY OF FORCED MONEY REGULATION IN THE STATE ADMINISTRATIVE COURT: NORMATIVE ANALYSIS OF IMPLEMENTATION MECHANISMS - Ferio Wabarca Hutabarat; Shinta Hadiyantina; Sudarsono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The regulation of forced money (dwangsom) within the State Administrative Court is an important instrument to ensure compliance of state administrative officials with court decisions that have permanent legal force. However, until now the regulations governing the mechanism for the implementation of forced money in the PTUN are still unclear, so it often causes obstacles in the practice of execution. This study aims to analyze the urgency of the regulation of forced money in the State Administrative Court by focusing on the implementation mechanism so that it can be implemented effectively. The research method used is a prescriptive method with a normative approach, namely examining applicable laws and regulations, legal doctrines, and relevant court decisions. The results of the study show that the absence of strict regulations regarding the implementation of forced money creates legal uncertainty and has the potential to weaken the function of the PTUN as judicial control over government administrative actions. Therefore, a more comprehensive regulation is needed regarding the mechanisms, procedures, and parameters of the implementation of forced money in order to provide legal certainty, ensure the effectiveness of the execution of decisions, and strengthen the principle of the rule of law in the administration of government.